2022
DOI: 10.1002/jsfa.12116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of spirulina loaded chitosan nanoparticles from prawn, Macrobrachium nipponense shell for extending the shelf life of pike‐perch (Sander lucioperca) fillet during refrigerated storage

Abstract: BACKGROUND This study was aimed to synthesize polymeric chitosan nanoparticles (CSNPs) from Macrobrachium nipponense shells using sodium triphosphate (TPP) as a crosslinker that was incorporated with spirulina extract (SPE) to improve the shelf life of pike‐perch during refrigerated storage (4 °C). RESULTS The encapsulation efficiency (EE) of SPE‐loaded CSNPs decreased from 67% to 32%, and loading capacity (LC) was increased (10–14%) depending on their loaded SPE concentrations. The initial burst effect, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
(245 reference statements)
0
4
0
Order By: Relevance
“…Chitosan-coated liposomes were prepared by mixing liposomes (SP-LP) with the chitosan solution (0.4% w/v chitosan in 1% v/v acetic acid) at a ratio of 1:1 under constant stirring (100 rpm) for 2 h at room temperature. The characterization of liposomal spirulina peptides (mean particle size, zeta potential, encapsulation e ciency (EE%), and storage stability) was performed as in our previous work (Karimzadeh et al, 2023).…”
Section: Preparation Of Spirulina Low-molecular-weight Peptides (Sps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan-coated liposomes were prepared by mixing liposomes (SP-LP) with the chitosan solution (0.4% w/v chitosan in 1% v/v acetic acid) at a ratio of 1:1 under constant stirring (100 rpm) for 2 h at room temperature. The characterization of liposomal spirulina peptides (mean particle size, zeta potential, encapsulation e ciency (EE%), and storage stability) was performed as in our previous work (Karimzadeh et al, 2023).…”
Section: Preparation Of Spirulina Low-molecular-weight Peptides (Sps)mentioning
confidence: 99%
“…At regular intervals, a de nite volume (3 mL) was withdrawn and replaced with an equal volume of fresh phosphate buffer solution. The amount of SP release was measured using total phenolic content by UV-Vis spectrometer (Karimzadeh et al, 2023).…”
Section: Release Studiesmentioning
confidence: 99%
“…SPR was safely used in Africa for several years [ 15 ]. SPR is a nutritionally enriched algae that have been globally cultivated as a dietary supplement, owing to its versatile biological and nutritional profile [ 16 ]. It is highly rich in nutrients, phytochemicals, proteins, and carbohydrates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that carotenoids and chlorophyll can be used to combat skin aging and protect the skin against UV-induced photo-oxidation [ 14 , 23 ]. Thus, SPR has several pharmacological activities, such as antimicrobial, antioxidant, antihypertensive, anti-inflammatory, immunomodulatory, and anticancerogenic properties [ 16 , 24 ]. These attributes make SPR an attractive ingredient, especially for the formulation of green and ecofriendly cosmetics [ 15 ].…”
Section: Introductionmentioning
confidence: 99%